Too early, too late: Timeliness of child vaccination in the Philippines - Valerie Gilbert Ulep; Jhanna Uy (Philippine Institute for Development Studies (PIDS), 2019)
The Philippine Expanded Program for Immunization has focused primarily on immunization coverage as their metric for performance. However, an equally important indicator of effective vaccine delivery remains unmeasured - the timeliness of administration. National Expanded Programs on Immunization should aim for both high immunization coverage levels and timely administration of vaccines - not early, not late. In this paper, we estimated the coverage and timeliness of routine childhood vaccination in the Philippines from 1993 to 2017 using six rounds of the National Demographic Health Survey. The major findings of the study are: (a) coverage for routine childhood vaccination fluctuated over the last 25 years, a trend not usually observed in most other countries like those in ASEAN. In 2014, the basic vaccination coverage in the Philippines dipped to 65%, the lowest level since 1990; (b) the provision of routine childhood vaccination is predominantly public; about 95% of vaccinated children obtained their vaccines from public facilities despite the large and increasing number of private facilities; (c) a large percentage of children, albeit vaccinated, had untimely administration. The percentage of timely administration among vaccinated children ranged from 38% to 65%. Only 10% had complete and timely basic vaccination. Overall, the Philippine EPI has shown inconsistent performance in both coverage and timeliness in the past two decades. The findings are critical inputs to a more comprehensive assessment of the EPI. It should provide insights in streamlining the delivery and financing mechanism of the EPI to rapidly expand coverage and to promote timely vaccination.
Keywords: 330; Expanded Program for Immunization; coverage; timeliness; Philippines